Forward on Shared Paths: Josef Pieper on the Importance of Common Language for Justice and Interdisciplinary Learning - Warne, Nathaniel A. (Philosophy, theology and the sciences, 2018)
This paper draws on the work of 20th century philosopher Josef Pieper (1904–1997) and explores the potential risks that follow from the estrangement of language from truth and reality. Extending from this discussion, the paper will make a connection between two medieval virtues, docility and justice. To do this I first look at the relationship between language, the mystery of truth and reality, and explicate the dangers of the sophistry to which Pieper draws attention in his work. The paper then connects the virtue of docility to a discussion of language and mystery by bringing out one of the key features of this virtue, which is the perfection of habits of openness through the free exchange of ideas in dialogue. This openness consists not only in being open to others' ideas, but also in being open to the errors in one's own ideas. For Pieper, the fundamental form of speech is dialogue, which develops in the context of relationships. This includes dialogue between fields of study, for example the sciences and humanities. Speech that has forgotten this ceases to be speech and ceases to be human. In the last section of the paper, I bring the above strands together to address the issue of terminology. What will be shown is that the corruption of language by sophistry amounts to constructed artificial terminology. 'Artificial terminology' is distinct from natural and historically developed language and can be damaging to dialogue and become a form of injustice.